Association Between TP53 Mutation and Prognosis in Wilms Tumor: A Meta-Analysis. (2nd November 2021) - Lizhi, Li; Rongdong, Huang; Shaohua, He; Yingquan, Kan; Huihuang, Xu; Shan, Lin; Kunbin, Tang; Di, Xu
Abstract: Background TP53 mutation has been suggested to have prognostic value for patients with Wilms tumor (WT), but the results are still controversial. Methods: Relevant studies published until August 1, 2019 were identified by searching PubMed, EMBASE and Cochrane Library. A random‐effect model was performed to assess pooled data. Begg's and Egger's test were used to evaluate the potential publication bias. Sensitivity analysis was used to evaluate the stability of results. Results: A total of seven eligible articles were included. There was no significant difference in the risk of death among patients with WT with different TP53 mutation status (odds ratio [OR] = 3.09, 95% confidence interval[CI]: 0.81–11.84). Combined hazard ratio (HR) suggested that TP53 mutation had an unfavorable impact on overall survival (OS) (HR = 4.17, 95% CI: 1.97–6.36) and disease-free survival (DFS) (HR = 2.23, 95% CI: 1.29–3.17) in WT. Conclusions: This meta-analysis demonstrates that TP53 mutations are associated with poorer prognosis in WT.